Numerical and Analytical Methods with MATLAB for Electrical Engineers - Bober W. William (Computational Mechanics and Applied Anallysis)
Combining academic and practical approaches to this important topic, Numerical and Analytical Methods with MATLAB® for Electrical Engineers is the ideal resource for electrical and computer engineering students. Based on a previous edition that was geared toward mechanical engineering students, this book expands many of the concepts presented in that book and replaces the original projects with new ones intended specifically for electrical engineering students. This book includes: • An introduction to the MATLAB® programming environment • Mathematical techniques for matrix algebra, root finding, integration, and differential equations • More advanced topics, including transform methods, signal processing, curve fitting, and optimization • An introduction to the MATLAB® graphical design environment, Simulink® Exploring the numerical methods that electrical engineers use for design analysis and testing, this book comprises standalone chapters outlining a course that also introduces students to computational methods and programming skills, using MATLAB® as the programming environment. Helping engineering students to develop a feel for structural programming—not just button-pushing with a software program—the illustrative examples and extensive assignments in this resource enable them to develop the necessary skills and then apply them to practical electrical engineering problems and cases.